SOME FACTORS RELATED TO REHABILITATION OUTCOMES IN PATIENTS WITH LUMBER DISC HERNIATION AT SAINT PAUL GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze factors related to rehabilitation treatment outcomes in patients with lumbar disc herniation at Functional Rehabilitation Department, Saint Paul General Hosptial in 2024.Subject and methods: A cross-sectional study analyzing factors associated with rehabilitation outcomes in patients with lumbar disc herniation.Result: Some factors related to rehabilitation treatment outcomes in patients with lumbar disc herniation include: mode of onset and circumstances of lumbar disc herniation occurrence; relationship between the severity of disc herniation and occupation; and association between gender and treatment outcomes prior to hospital discharge.Conclusion: Some factors related to rehabilitation treatment outcomes in patients with lumbar disc herniation include: mode of onset and circumstances of lumbar disc herniation occurrence, relationship between the severity of disc herniation and occupation and association between gender and treatment outcomes prior to hospital discharge.
Keywords: Lumbar disc herniation, treatment outcomes, some related factors.